For a theory of the stage performance. Hermeneutics and transformation of a literary text - Abuín, Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
This article will attempt to analyse the complex process of transduction or literary transformation in which the passing of the dramatic text to the stage performance is to be observed using two works of Meyerhold and Nieva. The performance sets a process of concretization in motion which to a great extent destroys the ambiguity in the literary text, converting the written linguistic signs into a variety of spectacular codes. Thus we find a twofold manipulation of the dramatic text that can delimit itself to a reading located in a contemporary reality and a consequent creative process which investigates the stage possibilities arising from the story which is to be told.